Ectoparasitos de aves na região de Ecótono Cerrado-Floresta Amazônica em Mato Grosso, Brasil - Silva, Dionice Leite Toledo da (2016)
Parasitism is the association between living organizms, where there is one-sidedness of benefits, being the host despoiled by the parasite, providing food and shelter. The objective of this study was to identify what types of ectoparasites that are associated with birds in relation to biological, ecological and habitat of hosts. Specifically, it sought to examine whether the infestation rates (parasite burden and prevalence) of ectoparasites vary in relation to taxonomic groups; the parasite load and the richness of ectoparasites are associated with biological factors (sex, age and reproductive period), morphological (wing relation/tail and body mass) and habitats (edge or inside the forest); and investigate whether the birds recaptured present a parasitic load and wealth of different ectoparasites than when captured for the first time. The study was conducted in a forest fragment area of ecotone Amazon Savanna-Forest in Ribeirao Cascalheira/MT in three sampling campaigns in February and June 2013 and October 2014. Birds captured and analyzed were labeled with metal washers supplied by CEMAVE / ICMBio. These birds, ectoparasites and collected information on biological data were removed (sex, age and reproductive period) and biometric (size of the wing/tail and body mass) as well as the occurrence of habitat (border or inside the forest). The collections of ectoparasites consisted blowing in plumage, followed by manual scavenging and application of permethrin. For the statistical analysis use the BioEstat 5.2® program, considered significant p values <0.05. Feather mites were the most ectoparasites found in birds, followed by lice, ticks and trombiculídeos. Among the hosts, families with higher parasite loads were Columbidae (Columbiformes, 20.3%), Thamnophilidae (Passeriformes, 15.7%) and Tyrannidae (Passeriformes, 13.1%). Birds outside the breeding season showed a significant difference to the parasitic load (X2 = 18,150 G = 1 (p) = 0.0001) compared with those who were in the reproductive period. There were no significant differences between the parasite load in relation to sex and age of the host. The amount of feather mites is independent of the size of the wing and tail of birds, but dependent on body mass. Birds captured in the edge of the forest had higher parasite burden and greater wealth in relation to the interior of the forest and recaptured had lower parasite load and lower wealth of ectoparasites in relation to captured. It was found that the most abundant birds ectoparasites in the study area were the feather mites.